Coherent control of symmetry breaking in transverse-field Ising chains using few-cycle pulses - Klimkin Nikolai D.; Rubtsov Alexey N.; Ivanov Misha (Nanophotonics)
Coherent control of quantum systems with phase-stable pulses offers enticing new opportunities for lightwave electronics. Here we extend this approach to many-body systems with spin degrees of freedom, demonstrating that a single few-cycle control pulse can create a sizable population asymmetry between the two degenerate polar ground states of the Ising model. This opens a route for femtosecond-scale data processing and storage, allowing one to control the final ground state of a correlated system in an all-optical way.